Efficacy and safety of Tafolecimab in Chinese patients with type 2 diabetes and hypercholesterolemia: a post-hoc analysis of pooled data from three phase 3 trials - Litong Qi; Hua Shen; Meng Chai; Beijian Chen; Yongming He; Xiaoxia Shi; Qiufang Lian; Wang Zhao; Yanling Qu; Lei Qian; Jianwei Zhang; Haoyu Li; et al. (Cardiovascular Diabetology)
Abstract Background This study evaluated the efficacy and safety of tafolecimab in patients with type 2 diabetes (T2D) and hypercholesterolemia by a post-hoc analysis of pooled data from three phase 3 trials. Methods Data from up to 12 weeks were analyzed to assess the effects of tafolecimab 450 mg every four weeks (Q4W) in patients with T2D and hypercholesterolemia. The primary endpoint was the percentage change in low-density lipoprotein cholesterol (LDL-C) levels from baseline to week 12. Secondary endpoints included the proportion of participants achieving LDL-C levels below 1.8 mmol/L at weeks 12, the proportion of patients achieving LDL-C ≥ 50% reduction and LDL-C < 1.4 mmol/L, as well as percentage changes from baseline to week 12 in non-high-density lipoprotein cholesterol (non-HDL-C), apolipoprotein B (apo B), lipoprotein(a) [Lp(a)], and triglyceride (TG) levels. Results The reduction in LDL-C from baseline was significantly greater in patients receiving tafolecimab than in those receiving placebo (estimated treatment difference: − 64.02%, 95% confidence interval: [− 68.08%, − 59.96%], P < 0.0001). The proportion of patients achieving a reduction of over 50% and an absolute LDL-C value below 1.4 mmol/L was significantly higher in the tafolecimab group than that in the placebo group (P < 0.0001). Furthermore, a significantly greater proportion of patients in the tafolecimab group achieved LDL-C levels below 1.8 mmol/L at week 12 compared to the placebo group (P < 0.0001). The tafolecimab group also showed significant reductions in TG, non-HDL-C, apo B, and Lp(a) from baseline to week 12 compared to the placebo group (all P < 0.001). The incidence of adverse events was generally similar between the two groups. Conclusion Tafolecimab 450 mg Q4W demonstrated a superior lipid-lowering efficacy and favorable safety profile compared to placebo. This suggests it could be a promising new treatment option for Chinese patients with T2D and hypercholesterolemia. Graphical abstract